(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The study was intended to investigate anti-diabetic efficacy of Aerva lanata by determining its α-amylase inhibition activity and in vitro uptake of glucose in adipose tissue and psoas muscle isolated from male Sprague Dawley (SD) rats. Aerva lanata is reported to have many traditional and Ayurvedic uses. Male SD rats (n=3) of 150 g were sacrificed and 250 mg of respective tissues were isolated for the study. Aerva lanata ethanolic extract (ALE) (5-20 mg/mL) showed 13.30 to 54.08% α-amylase inhibition activity. Glucose uptake studies in in vitro conditions were carried out in both adipose tissue and psoas muscle in different sets - tissue alone, tissue along with (Aerva lanata extract: 50µg, 100µg, 150µg, insulin: 25 mU/L, insulin: 50 mU/L and Aerva lanata extract: 50µg + insulin: 25 mU/L, Aerva lanata extract: 100µg + insulin: 25 mU/L, Aerva lanata extract: 150µg + insulin: 25 mU/L, Aerva lanata extract: 50µg + insulin: 50 mU/L, Aerva lanata extract: 100µg + insulin: 50 mU/L, Aerva lanata extract: 150µg + insulin: 50 mU/L). The rate of glucose uptake by insulin action in these tissues was stabilized by ethanolic extract of Aerva lanata and this shows synergetic activity of insulin and Aerva lanata.